2022
DOI: 10.3390/diagnostics12061387
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget Molecular Imaging in Metastatic Castration Resistant Adenocarcinoma Prostate Cancer with Therapy Induced Neuroendocrine Differentiation

Abstract: Neuroendocrine differentiation of prostate cancer (NEDPC) includes de novo presentation and secondary to epigenetic changes, referred as therapy-induced neuroendocrine prostate cancer (t-NEPC). Molecular imaging with prostate-specific membrane antigen (PSMA) and somatostatin analogues positron emission tomography (PET/CT) in NEDPC have not been validated. 18F-FDG (fluorodeoxyglucose) PET/CT has numerous limitations in prostate cancer (PCa) and the utility in NEDPC has only been reported in a few series of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…On the side note, it is important to mention that some patients, who were treated with either 177 Lu-PSMA or 225 Ac-PSMA or tandem therapy, do not show any treatment response at all due to tumors without PSMA expression or due to neuroendocrine differentiation. Neuroendocrine differentiation in PCa is mostly therapy-induced (17–30%); however, in some cases it develops de novo (0.5–2%) [ 58 ].…”
Section: Combination Therapymentioning
confidence: 99%
“…On the side note, it is important to mention that some patients, who were treated with either 177 Lu-PSMA or 225 Ac-PSMA or tandem therapy, do not show any treatment response at all due to tumors without PSMA expression or due to neuroendocrine differentiation. Neuroendocrine differentiation in PCa is mostly therapy-induced (17–30%); however, in some cases it develops de novo (0.5–2%) [ 58 ].…”
Section: Combination Therapymentioning
confidence: 99%
“…Spratt et al reported that 18 F‐FDG PET/CT had a high sensitivity in detecting distant metastases in a 23 NEPC patients cohort 12 . And a diagnostic study showed 18 F‐FDG was the optimum radiotracers for detecting NEPC lesions 23 . In comparison, our study provided the definitive pathological diagnosis and classification of NEPC.…”
Section: Discussionmentioning
confidence: 57%
“…12 And a diagnostic study showed 18 F-FDG was the optimum radiotracers for detecting NEPC lesions. 23 In comparison, our study provided the definitive pathological diagnosis and classification of NEPC. Of note, the correlation between high 18 F-FDG uptake and SCNC suggested the potential opportunities for 18 F-FDG PET/CT to assist in diagnosing histopathological subtypes.…”
Section: Discussionmentioning
confidence: 88%
“…Several reports support the possible high [ 18 F]FDG-avidity in cases of tiNED, particularly in soft tissue tumor lesions [39][40][41][42][43]. In a study that included 23 CRPC patients with "clinical NED" (elevated blood levels of chromogranin A), 22% of 510 bone metastases and 95% of 82 soft tissue metastases were [ 18 F]FDG-avid [40].…”
Section: Discussionmentioning
confidence: 96%